2007
DOI: 10.1080/10473289.2007.10465312
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Soil Contaminated with Pyrene Using Ground Nanoscale Zero-Valent Iron

Abstract: The sites contaminated with recalcitrant polycyclic aromatic hydrocarbons (PAHs) are serious environmental problems ubiquitously. Some PAHs have proven to be carcinogenic and hazardous. Therefore, the innovative PAH in situ remediation technologies have to be developed instantaneously. Recently, the nanoscale zero-valent iron (ZVI) particles have been successfully applied for dechlorination of organic pollutants in water, yet little research has investigated for the soil remediation so far. The objective in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…The addition of zero-valent iron enhanced the anaerobic degradation of PAH. Zero-valent iron can serve as the electron donor and was capable of efficiently removing PAH (Chang et al 2007b). Liu et al (2000) found PAH, DEHP, nonylphenol, and heavy metals in samples collected from various Taiwanese rivers and we therefore studied the effects of these pollutants on the anaerobic degradation of PAH in mangrove sediment.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of zero-valent iron enhanced the anaerobic degradation of PAH. Zero-valent iron can serve as the electron donor and was capable of efficiently removing PAH (Chang et al 2007b). Liu et al (2000) found PAH, DEHP, nonylphenol, and heavy metals in samples collected from various Taiwanese rivers and we therefore studied the effects of these pollutants on the anaerobic degradation of PAH in mangrove sediment.…”
Section: Resultsmentioning
confidence: 99%
“…Anaerobic degradation of PAHs is also inhibited by the addition of molybdate (a selective inhibitor of sulfate-reducing bacteria), BESA (a selective inhibitor of methanogen) and vancomycin (a selective inhibitor of eubacteria) (Lovely and Philips 1988;Distefano et al 1992), indicating that sulfate-reducing and methanogenic bacteria are involved in the degradation of PAHs. The addition of cellulose and iron increased the anaerobic degradation of PAHs by aerobic respiration stimulation and by acting as an electron donor, respectively (Quantin et al 2005;Chang et al 2007). These results also show that the rates of anaerobic phenanthrene degradation were greater than the rates of pyrene degradation (Chang et al 2008).…”
Section: Case Studiesmentioning
confidence: 98%
“…The half-life of degradation (DT 50 ) was calculated from Equation (5). [30,32] All experimental data were compared by analysis of variances (ANOVA) and processed using the statistical software SPSS 11.5 of treatments and control samples. Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…The initial pH and PCB77 concentration were 6.8 and 5 mg¢L ¡1 , respectively. Then 10 mL of PCB77 solution was sampled at different time points (10,30,60,90,120 and 240 min). The solution was shaken with 10 mL of hexane for 10 min, and this procedure was repeated.…”
Section: Nanoparticlesmentioning
confidence: 99%